A Cost Analysis of the Impact of a New Intravenous Antihypertensive in Managing Perioperative Blood Pressure during Cardiac Surgery. Issue 3 (August 2014) - Aronson, Solomon; Dasta, Joseph F.; Levy, Jerrold H.; Lumb, Philip D.; Fontes, Manuel; Wang, Yamei; Crothers, Tracy A.; Sulham, Katherine A.; Navetta, Marco S.
Abstract: Objective: To examine the impact of intravenous antihypertensive selection on hospital health resource utilization using data from the Evaluation of CLevidipine In the Perioperative Treatment of Hypertension Assessing Safety Events (ECLIPSE) trials. Methods: Analysis of ECLIPSE trial data comparing clevidipine to nitroglycerin, sodium nitroprusside, and nicardipine and unit costs based on the Premier Hospital database to assess surgery duration, time to extubation, and length of stay (LOS) with the associated cost. Results: A total of 1414 patients from the ECLIPSE trials and the Premier hospital database were included for analysis. The duration of surgery and postoperative LOS were similar across groups. The time from chest closure to extubation was shorter in patients receiving clevidipine group compared with the pooled comparator group (median 7.0 vs 7.6 hours, P = 0.04). There was shorter intensive care unit (ICU) LOS in the clevidipine group versus the nitroglycerin group (median 27.2 vs 33.0 hours, P = 0.03). A trend toward reduced ICU LOS was also seen in the clevidipine compared with the pooled comparator group (median 32.3 vs 43.5 hours, P = 0.06). The costs for ICU LOS and time to extubation were lower with clevidipine than with the comparators, with median cost savings of $887 and $34, respectively, compared with the pooled comparator group, for a median cost savings of $921 per patient. Conclusions: Health resource utilization across therapeutic alternatives can be derived from an analysis of standard costs from hospital financial data to matched utilization metrics as part of a randomized controlled trial. In cardiac surgical patients, intravenous antihypertensive selection was associated with a shorter time to extubation in the ICU and a shorter ICU stay compared with pooled comparators, which in turn may decrease total costs.